A taxonomic review of Korean species of the genus Philhygra Mulsant & Rey (Coleoptera: Staphylinidae: Aleocharinae) - Lee, Seung-Gyu; Ahn, Kee-Jeong (Zootaxa, 2012)
A taxonomic review of Korean species of the athetine genus Philhygra Mulsant & Rey, 1873 is presented. Seven species are recognized, two of which, P. pseudoelongatula (Bernhauer, 1907) and P. sparsa (Bernhauer, 1907), are new to the Korean Peninsula. A key, descriptions and illustrations of diagnostic characters are provided.